Pneumococcal Meningitis - Kelly Di Dier; Marc Lemmerling (Journal of the Belgian Society of Radiology, 2022)
Teaching Point: Spontaneous, atraumatic pneumocephalus is a rare presentation of pneumococcal meningitis.